The Effect of Local Government Spending Behavior on Local Economic Growth in Indonesia - Arsy Fajriar; Khoirunurrofik Khoirunurrofik (Universitas Negeri Malang, 2025)
Based on the relevant theory, it is clear that the effect of government expenditure on local economic growth depends not only on government size but also on its timeliness. Slow and back-loaded expenditure will reduce its impact on the economy. Through the dynamic panel data methods, this study comprehensively measures the effect of local spending behavior in the form of year-end spending spikes on local economic growth in Indonesia. This study uses a new database that covers 462 districts/cities in Indonesia, from 2016 to 2019. According to the estimation findings, an increase in year-end spending spikes by one percentage point would reduce real GRDP growth by 0.0590 percentage points and is statistically significant at 5%.